2018
DOI: 10.1002/cam4.1496
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HACE1 in gastric cancer inhibits tumor aggressiveness by impeding cell proliferation and migration

Abstract: HACE1 E3 ligase was discovered to be down‐regulated in several cancers while its role in regulating tumors was merely understood. This study aimed to explore the specific effect of HACE1 played in gastric tumorigenesis and its potential mechanism. HACE1's expression was found significantly lower in gastric cancer tissues compared with the adjacent normal tissues (P < 0.001). Its protein level in gastric cancer negatively correlated to tumor pathological differentiation (P = 0.019). And in gastric cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Finally, HECT E3 ubiquitin ligases are also involved in more rare cancers, such as gastric cancer, transitional cell carcinoma, esophageal squamous cell carcinoma (ESCC), pancreatic cancer and thyroid cancer. For example, HACE1 expression was shown to be suppressed in gastric cancer tissues, whereas its experimental overexpression can inhibit tumor proliferation, migration and enhance cell apoptosis (Chen et al, 2018). In contrast, NEDD4 expression is upregulated in advanced gastric cancer tissues, with a concurrent increased probability of metastasis (Ye et al, 2014).…”
Section: Cancersmentioning
confidence: 99%
“…Finally, HECT E3 ubiquitin ligases are also involved in more rare cancers, such as gastric cancer, transitional cell carcinoma, esophageal squamous cell carcinoma (ESCC), pancreatic cancer and thyroid cancer. For example, HACE1 expression was shown to be suppressed in gastric cancer tissues, whereas its experimental overexpression can inhibit tumor proliferation, migration and enhance cell apoptosis (Chen et al, 2018). In contrast, NEDD4 expression is upregulated in advanced gastric cancer tissues, with a concurrent increased probability of metastasis (Ye et al, 2014).…”
Section: Cancersmentioning
confidence: 99%
“…HACE1 downregulation has been identified in numerous types of cancer, including hepatocellular carcinoma, breast cancer, colorectal cancer, gastric cancer and leukaemia (5,11). Previous studies have demonstrated that decreased expression or deletion of HACE1 caused by HACE1 methylation or ubiquitination is associated with the occurrence and invasion of various types of carcinoma (18,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…HACE1 was first studied in Wilms' tumour and was later identified to be frequently lost or downregulated in a variety of tumours. Its role in tumour suppression has been extensively investigated, and a number of studies have indicated that HACE1 can restrain reactive oxygen species generation, control cell fate by regulating TNF receptor superfamily member 1A, and impede tumour growth by accelerating the ubiquitination of Rac family small GTPase 1 (11,25,26). Notably, it has been reported that HACE1 acts as a tumour suppressor by ubiquitinating OPTN, and that it activates selective autophagy (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high levels of EPHA7 may have the effect of sequestering microRNAs and reducing proliferation in other cancers [31]. HACE1 is an E3 ligase downregulated in several cancers, including gastric cancer and breast cancer, and was found to inhibit the Wnt/β-catenin pathway, thereby playing a role in suppressing tumorigenesis [32, 33]. The pathway involving TRIP11 and triiodothyronine is necessary for localization of TRIP11 to the nucleus and was found to be disrupted in renal cell cancer, leading to progression [34].…”
Section: Discussionmentioning
confidence: 99%